The quantitative relationship between fracture toughness and impact toughness in high-strength steels. (15th April 2019) - Li, H.F.; Duan, Q.Q.; Zhang, P.; Zhou, X.H.; Wang, B.; Zhang, Z.F.
Highlights: We propose the quantitative relationship between fracture toughness and impact toughness in high-strength steels. Both impact toughness and fracture toughness of materials obey the minimum energy density criterion. The relation is affected by two aspects: the energy consumption pattern and specimen size. It would provide a more economical and faster way to quantitatively predict the fracture toughness of high-strength steels. Abstract: In this paper, the fracture toughness and impact toughness were systematically studied in high-strength steels. The results show that the two types of toughness are both the representative of the competition between flat fracture and shear fracture, which follows the minimum energy density criterion. Accordingly, we established the quantitative relation between impact toughness and fracture toughness in high-strength steels through theoretical derivations. The relation is affected by two aspects: the energy consumption pattern and specimen size. It would provide a more economical and faster way to quantitatively predict the fracture toughness of high-strength steels, which can be further applied to some new materials such as high-entropy alloys, nanostructured materials and metallic glasses.